2017
DOI: 10.1002/celc.201600902
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Lateral Flow Devices: Towards Rapid Immunomagnetic Assays

Abstract: Paper has been used for a long time in the production of low‐cost point‐of‐care (POC) detection devices, most of which rely on the detection of colored bands by the user. However, test strips rarely provide the quantitative detection of biomarkers in clinical samples. In contrast, electrochemical detection enables quantitative detection in paper‐based immunoassays. Here, we demonstrate the production of a simple and economical lateral‐flow electrode device using only screen printing. Contrary to previous work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…28 Approaches to improve label capture and/or label detection have been developed. For instance, new contrast labels including quantum dots, 22 upconverting phosphor reporters, 20 magnetic particles, 29, 30 and surface-enhanced Raman scattering GNPs 25 have all been applied. Isotachophoresis 24 - and dialysis 26 -based sample treatments can preconcentrate analyte and improve label capture.…”
mentioning
confidence: 99%
“…28 Approaches to improve label capture and/or label detection have been developed. For instance, new contrast labels including quantum dots, 22 upconverting phosphor reporters, 20 magnetic particles, 29, 30 and surface-enhanced Raman scattering GNPs 25 have all been applied. Isotachophoresis 24 - and dialysis 26 -based sample treatments can preconcentrate analyte and improve label capture.…”
mentioning
confidence: 99%
“…Nevertheless, all the above fabrication techniques are based on placing the electrodes on the surface or underneath the lateral-flow membrane. Ruiz-Vega et al (Ruiz-Vega et al, 2017) recently demonstrated the direct integration of micropatterned electrodes printed onto a lateralflow membrane for the fabrication of a fully integrated electrochemical lateral-flow test for the detection of myeloperoxidase. A three-electrode system, composed of a silver reference electrode and graphite working/counter electrodes, was screen printed directly on the lateralflow membrane.…”
Section: Lateral-flow Membrane-based Strip Testsmentioning
confidence: 99%
“…The paper-based bioanalytical devices use capillary forces to drive the lateral flow of a liquid sample (i.e., lateral flow immunochromatographic assays or lateral flow tests) [155,156]. Based on the generated color, lateral flow tests can provide qualitative or semi-quantitative information [157]. Quantitative measurements can also be obtained with electrochemical paper-based analytical devices (ePADs) that use the photolithography to create microfluidic channels on the filter paper ( Figure 6a) [55].…”
Section: Paper-based Biosensorsmentioning
confidence: 99%
“…Spotting the analyte-specific enzymes (e.g., GOx, lactate oxidase or LOx, and uricase) helps determine the concentration of glucose, lactate, and uric acid, with a limit of detection of 0.21 ± 0.02 mM, 0.36 ± 0.03 mM, and 1.38 ± 0.13 mM, respectively. As a close distance between the working and reference electrodes minimizes the effect from uncompensated resistance between the two electrodes, screen printing that requires a stencil to pattern the electrodes limits the achievable maximum resolution [157][158][159][160].…”
Section: Paper-based Biosensorsmentioning
confidence: 99%